Bioactividad de la fruta y semilla de Terminalia catappa Linn (Research, Society and Development, 2020)
The bioactive properties of unconventional fruits have been of interest in recent research. The objective of this study was to evaluate the bioactivity of Terminalia catappa Linn fruit and seed through its antioxidant and antimicrobial activity against pathogenic microorganisms. The fruit and the seed were analyzed for the physical-chemical parameters of pH, aw, humidity, ashes, carbohydrates, proteins and lipids. After drying, pulp and almond flours were evaluated for bioactivity (total phenolics, tannins, anthocyanins and flavonoids and antioxidant-DPPH) and antimicrobial activity. The fruit had a higher carbohydrate content (15.65%), while the seed was characterized by high lipid content (48.52% ± 0.31) and protein (26.40% ± 0.10). The pulp flour showed significant amounts of tannins (1662.68 mg.100-1 g ± 1.27) and antimicrobial activity inhibiting Staphylococcus aureus, Pseudomonas putida, Pseudomonas aeruginosa, Clostridium perfringens and Listeria monocytogenes. The seed flour presented antioxidant activity (46.05 mg.100-1 g ± 0.23), but did not present inhibitory power against the tested bacterial strains. Terminalia catappa Linn fruit can be an alternative new ingredient with natural antioxidant action.